ON THE MATHEMATICS PROBLEM OF MULTILAYERED DIELECTRIC SYSTEMS IN THE CLASSICAL ELECTRODYNAMIC - Yu. I. Hudak (Российский технологический журнал)
Solving numerous problems of wave propagation in inhomogeneous medium in optics and radio-physics involves layered media models. Unfortunately even for two-layer systems there is no known exhaustive classification of such systems presenting their “phase image”. In the paper the solution of direct problem of flat electromagnetic wave propagation in N-layer dielectric media derived in the form of quasi-trigonometric polynomials. Exact expressions for reflectivity factor and transmission factor are given. The algorithm of inverse problem solution providing layered media physical parameters from amplitude reflectivity factor is devised. The solution is proved to be unique. New substantial notions allow handling the problem in an easier and more natural way. In the cases of a few layers, explicit solutions for translucence and anti-translucence problems at a given frequency and in a fixed frequency range are found. The comprehensive classification of two-layer systems is based on the structure of the planar graph in the parameter space having 19 inherent graph nodes, 66 graph edges and 48 facets.